Effect of (R)‐salbutamol on the switch of phenotype and metabolic pattern in LPS‐induced macrophage cells. Issue 1 (3rd November 2019) - Wang, Shanping; Liu, Fei; Tan, Keai Sinn; Ser, Hooi‐Leng; Tan, Loh Teng‐Hern; Lee, Learn‐Han; Tan, Wen
Abstract: Evidence demonstrates that M1 macrophage polarization promotes inflammatory disease. Here, we discovered that (R)‐salbutamol, a β2 receptor agonist, inhibits and reprograms the cellular metabolism of RAW264.7 macrophages. (R)‐salbutamol significantly inhibited LPS‐induced M1 macrophage polarization and downregulated expressions of typical M1 macrophage cytokines, including monocyte chemotactic protein‐1 (MCP‐1), interleukin‐1β (IL‐1β) and tumour necrosis factor α (TNF‐α). Also, (R)‐salbutamol significantly decreased the production of inducible nitric oxide synthase (iNOS), nitric oxide (NO) and reactive oxygen species (ROS), while increasing the reduced glutathione (GSH)/oxidized glutathione (GSSG) ratio. In contrast, (S)‐salbutamol increased the production of NO and ROS. Bioenergetic profiles showed that (R)‐salbutamol significantly reduced aerobic glycolysis and enhanced mitochondrial respiration. Untargeted metabolomics analysis demonstrated that (R)‐salbutamol modulated metabolic pathways, of which three metabolic pathways, namely, (a) phenylalanine metabolism, (b) the pentose phosphate pathway and (c) glycerophospholipid metabolism were the most noticeably impacted pathways. The effects of (R)‐salbutamol on M1 polarization were inhibited by a specific β2 receptor antagonist, ICI‐118551. These findings demonstrated that (R)‐salbutamol inhibits the M1 phenotype by downregulating aerobic glycolysis and glycerophospholipid metabolism, which may propose (R)‐salbutamol as the major pharmacologically active component of racemic salbutamol for the treatment of inflammatory diseases and highlight the medicinal value of (R)‐salbutamol.